The regulation of artificial intelligences in the European Union: stages, challenges, prospects - Buchynska, A. Yo (Аналітично-порівняльне правознавство, 2025)
The article examines the process of forming a legal definition of artificial intelligence (AI) in the context of the European regulatory approach, in particular through the prism of the recently adopted Regulation (EU) 2024/1869 on harmonised rules on artificial intelligence (AI Act). It is emphasized that the rapid development of digital technologies, the multi-vector application of AI and its interdisciplinary nature create significant challenges for legal regulation. The author analyzes the regulatory, ethical and political prerequisites that contributed to the gradual formation of a conceptual vision of AI in the European Union, starting with the political initiatives of 2018, the creation of the High-Level Group on Artificial Intelligence and the publication of the 2020 “White Paper on Artificial Intelligence. A European approach to excellence and trust”, which outlined a strategic vision for the development of AI in the EU. Particular attention is paid to the legal definition of the concept of “artificial intelligence system” in Article 3 of the AI Act, which combines technological neutrality with a risk-based approach. The article highlights how the European model of AI regulation is based on two fundamental principles – ensuring technological leadership in the world (excellence) and establishing trust, such an approach involves stimulating innovation and implementing advanced solutions, and on the other hand, respecting human rights, ethical standards and democratic values. The main stages of the rule-making process, key positions of the European Union institutions (Commission, Council, Parliament), as well as political compromises that preceded the adoption of the final text of the Regulation in 2024 are considered. The new obligations of Member States to establish institutional oversight at the national level, adapt national legislation to the requirements of the Regulation and introduce liability mechanisms for violations of the provisions of this act are analyzed. As a result, it was concluded that Regulation (EU) 2024/1869 is the first attempt to create a comprehensive regulatory framework for regulating artificial intelligence at the supranational level, which not only enshrines its legal definition, but also establishes the principles of safe, transparent and ethically responsible use of AI in the context of digital transformation.